Integrating Akan traditional art to enhance conceptual understanding in mathematics: Perspectives of educators and artisans - AMOAKO ATTA, SETH (Journal of Interdisciplinary Studies in Education, 2024)
The purpose of the study was to investigate how the Akan culture promotes conceptual understanding of geometry in senior high schools. The study area was the Ashanti region, which houses a chunk of the Akan people. The targeted population for the study included experienced mathematics teachers and people well-versed in Akan traditional art. Using purposive and snowball sampling methods, ten participants were recruited, including seven experienced mathematics teachers and three craftsmen. Data was collected through interviews to elicit in-depth information from participants using a semi-structured interview guide. The data was analysed using thematic analysis. One major theme and four sub-themes were identified, indicating that to achieve conceptual understanding, teachers make use of learners’ experiences as they build new knowledge, which enables learners to transfer the knowledge to new situations as they apply the knowledge. We therefore conclude that the Akan culture has connections with geometry, and teachers are encouraged to adapt the school geometry to the Akan culture. We also encourage more research in the area of ethnomathematics to widen the scope.